2016
DOI: 10.1002/oby.21560
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of serum odd‐ and branched‐chain fatty acids in patients with excess weight

Abstract: Objective: While small amounts of odd-chain fatty acids (OCFAs) and branched-chain fatty acids (BCFAs) were known to be present in mammals, it was quite recently that they were shown to play an important role in human health. However, still little is known on OCFA and BCFA profiles in subjects who have obesity. The aim of this study was to verify whether obesity is associated with changes in serum OCFA and BCFA profiles. Methods: Serum content of fatty acids was determined by gas chromatography-mass spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 39 publications
7
93
1
1
Order By: Relevance
“…Pentadecanoic acid and heptadecanoic acid are reported to be negatively associated with several disease outcomes, including diabetes, atherosclerosis, and cardiovascular diseases (52). Our results concur with Kratz, Baars, and Guyenet (53), who reviewed 16 studies and reported that dairy fats might be associated with lower obesity risk, although Mika et al (54) found no difference in serum levels between individuals with and without obesity. This study suggests that the dietary source of the SFAs might determine their implication in obesity.…”
Section: Discussionsupporting
confidence: 92%
“…Pentadecanoic acid and heptadecanoic acid are reported to be negatively associated with several disease outcomes, including diabetes, atherosclerosis, and cardiovascular diseases (52). Our results concur with Kratz, Baars, and Guyenet (53), who reviewed 16 studies and reported that dairy fats might be associated with lower obesity risk, although Mika et al (54) found no difference in serum levels between individuals with and without obesity. This study suggests that the dietary source of the SFAs might determine their implication in obesity.…”
Section: Discussionsupporting
confidence: 92%
“…Intriguingly, del Genio et al . found lower contents of MUFAs, especially 16:1 and 18:1, and elevated levels of PUFAs within PHL in erythrocyte membranes from obese subjects, whereas our previous study of morbidly obese persons demonstrated an increase in serum MUFAs and a decrease in serum PUFAs . Also, Cordero et al .…”
Section: Lipid Alterations In Obesitycontrasting
confidence: 85%
“…FAs are a diverse group of compounds differing in terms of chain length, degree of saturation thereof and metabolic effects . Both the results of our previous studies and data published by other researchers imply that obese subjects may display significant changes in their FA profiles, which may exert significant effects on their metabolism and general health status. Also, the composition of PHLs in blood cells was demonstrated to be altered in obese patients .…”
Section: Lipid Alterations In Obesitysupporting
confidence: 53%
See 2 more Smart Citations